Digital Leadership of School Administrators Affecting Technology Utilization in Learning Management of Teachers under Songkhla Primary Educational Service Area Office 1 - Wannapairo, Suntaree; Kiyah, Subeena (Journal of Education Studies, Chulalongkorn University, 2025)
The objectives of this research were to: 1) study digital leadership of school administrators, 2) examine teachers' technology utilization in learning management, and 3) create a formula predicting the influence of digital leadership of school administrators affecting technology utilization in learning management of teachers. The sample group consisted of 285 teachers. Data were analyzed using mean, standard deviation, and multiple regression analysis. The results revealed that: 1) the overall digital leadership of administrators was high, 2) teachers' technology utilization in learning management was also high, and 3) multiple regression analysis of digital leadership of school administrators affecting technology utilization in learning management of teachers indicated that four variables collectively accounted for 67.80% of the variance in teachers' technology utilization, with statistical significance at the .001 level. These variables were creating a digital learning culture (X2), digital citizenship (X4), digital technology skills (X3), and digital vision (X1). The multiple regression equation can be constructed in raw-score form as: Ŷ = .936 + .273 (creating a digital learning culture) + .194 (digital citizenship) + .167 (digital technology skills) + .153 (digital vision), and in standard-score form as: Ẑ = .305 (creating a digital learning culture) + .230 (digital citizenship) + .215 (digital technology skills) + .178 (digital vision).